2019
DOI: 10.3989/gya.0570181
|View full text |Cite
|
Sign up to set email alerts
|

Stability and volatile oxidation compounds of grape seed, flax seed and black cumin seed cold-pressed oils as affected by thermal oxidation

Abstract: The old-pressed oils (CPO) from grape seeds (GSO), flax seeds (FSO) and black cumin seeds (BSO) were analyzed for their fatty acid profiles, tocopherols, total phenolics, bioactives and phenolic compositions. The stability of CPO under thermal oxidation conditions was evaluated. The main fatty acid in FSO was linolenic acid (56.5% of total fatty acids); while GSO and BSO were rich in linoleic acid, which accounted for 66.8 and 56.8%, respectively. GSO was rich in ?-tocopherol (123.0 mg/kg), while ?-tocopherol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 54 publications
1
21
1
Order By: Relevance
“…Furthermore, a comparison of RA with ROA indicated the influence of roasting on the stability of the oil. PV results from the other oils, including MT, in most cases, were similar to those reported in other studies [ 5 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, a comparison of RA with ROA indicated the influence of roasting on the stability of the oil. PV results from the other oils, including MT, in most cases, were similar to those reported in other studies [ 5 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…Besides that, it was also determined that the storage temperature significantly affected the storage stability of seed oils. Some of the results obtained from the present study differ from the values reported in the literature (Kiralan et al., 2019). It is believed that these differences might arise from the differences in cold‐pressed herbal oils’ quality, production technology, storage period, and oxidative stabilities.…”
Section: Resultscontrasting
confidence: 99%
“…In their study, Kiralan et al. (2019) similarly stored the cold‐pressed flaxseed, black cumin seed, and grape seed oils at 60°C for 18 days and reported that the highest increase was observed in flaxseed oil and the lowest increase in black cumin seed oil. In another study, Oro et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2012), Johnson‐Ajinwo and Li (2014), Kiralan et al. (2019), Lutterodt et al. (2010), Mazaheri et al.…”
Section: Fat‐soluble Bioactives In Specialty Seed Oilsmentioning
confidence: 99%
“…Specialty seeds are highly nutritious and provide macronutrients, micronutrients, fat‐soluble bioactives, and polyphenolic health‐promoting compounds (Chen et al., 2019a; Ciftci et al., 2012; Dhyani et al., 2019; Ghaleshahi et al., 2020; Kiczorowska et al., 2019; Kiralan et al., 2019; Korean National Institute of Agricultural Sciences, 2016; Leizer et al., 2000; Liu et al., 2019; Melo et al., 2019; Nergiz & Ötleş, 1993; Rahman et al., 2017; Rezig et al., 2012; Stevenson et al., 2007; Suri et al., 2019; Tang et al., 2016; USDA, 2019; Xu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%